Social dilemma to AI dilemma: what’s next - Abdul Molok, Nurul Nuha; Mohd Nordin, Mohd Fahmi (Karya Ilham Publishing, 2025)
This study examines past and present social media and artificial intelligence (AI) dilemmas and potential future challenges. It is a dilemma since these technologies are considered as a double-edged sword as there are positive and negative outcomes. The conceptual study explores both dilemmas by reviewing and analyzing sources from academia, government and the industry, and its findings indicate that the rapid pace of AI development is outpacing the establishment of ethical guidelines, making internet governance more difficult. Cyber safety and security issues such as the creation of realistic deepfakes, sophisticated manipulation of public opinion, and the erosion of reality are major concerns. The conclusion is that if humanity struggled to manage the implications of AI-driven algorithms in social media and ill-prepared for Generative AI, we will face the risks of an entirely different magnitude, potentially impacting our ability to control our future and even our existence. Therefore, proactive actions and a focus on human well-being in technology design and governance are crucial, in order to be prepared for the future dilemma